1994
DOI: 10.1523/jneurosci.14-12-07594.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin depletion on vibrissa-related patterns of thalamic afferents in the rat's somatosensory cortex

Abstract: To investigate the role of 5-HT in the development of the somatosensory cortex, this amine was depleted in newborn (P-0) rats with a single subcutaneous injection of the toxin 5,7-dihydroxytryptamine (5,7-DHT) and thalamocortical organization was assayed by application of the carbocyanine dye Di-I to the thalamocortical radiations or ventrobasal thalamus, or by staining cortical sections for AChE or cytochrome oxidase (CO). High-performance liquid chromatographic analysis of cortices from animals killed on P-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 31 publications
6
92
0
Order By: Relevance
“…Lesion induced 5-HT innervation decreases were most dramatic in frontal cortex, a region that ordinarily contains a high density of 5-HT afferents from the raphe nuclei (Molliver, 1987;Molliver et al, 1990;Mamounas et al, 1991;Dori et al, 1996;Donovan et al, 2002). Remnants of 5-HT patches in layer IV of somatosensory cortex remained at PND 7, indicating that sequestration of serotonin by thalamocortical axons (Bennett-Clarke et al, 1991;Bennett-Clarke et al, 1994;Lebrand et al, 1996;Bennett-Clarke et al, 1997;Bruning and Liangos, 1997;Mansour-Robaey et al, 1998;Boylan et al, 2000a) persists after the neonatal 5,7-DHT lesions, despite the substantial reductions in cortical 5-HT innervation. Accumulation of 5-HT into thalamocortical terminals via SERT is likely the reason that citalopram binding was only mildly reduced in PND 7 and PND 15 mice after the lesion.…”
Section: Selective Serotonergic Depletionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion induced 5-HT innervation decreases were most dramatic in frontal cortex, a region that ordinarily contains a high density of 5-HT afferents from the raphe nuclei (Molliver, 1987;Molliver et al, 1990;Mamounas et al, 1991;Dori et al, 1996;Donovan et al, 2002). Remnants of 5-HT patches in layer IV of somatosensory cortex remained at PND 7, indicating that sequestration of serotonin by thalamocortical axons (Bennett-Clarke et al, 1991;Bennett-Clarke et al, 1994;Lebrand et al, 1996;Bennett-Clarke et al, 1997;Bruning and Liangos, 1997;Mansour-Robaey et al, 1998;Boylan et al, 2000a) persists after the neonatal 5,7-DHT lesions, despite the substantial reductions in cortical 5-HT innervation. Accumulation of 5-HT into thalamocortical terminals via SERT is likely the reason that citalopram binding was only mildly reduced in PND 7 and PND 15 mice after the lesion.…”
Section: Selective Serotonergic Depletionsmentioning
confidence: 99%
“…In cerebral cortical development, early manipulations of the serotonergic innervation lead to altered development and plasticity in sensory areas in a variety of species (Gu and Singer, 1995;Osterheld-Haas and Hornung, 1996;Janusonis et al, 2004). In rat, neonatal systemic depletion of the cortical serotonergic innervation delays thalamocortical patterning (Blue et al, 1991) and diminishes the size of the barrel field area during the first postnatal week (Bennett-Clarke et al, 1994). Interestingly, increased serotonin neurotransmission during the critical period also alters barrel field development (Vitalis et al, 1998;Boylan et al, 2000b;Salichon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The rodent somatosensory cortex lends itself to assessments of 5-HT roles in neocortical development and plasticity, because of its one-to-one correspondence between each whisker on the snout of the animal and its barrel-like representation in the somatosensory cortex (for review, see Killackey et al, 1995;Rice, 1995). Pharmacologically induced 5-HT depletion at birth yields smaller barrels, but does not prevent the formation of the barrel pattern itself (Blue et al, 1991;Bennett-Clarke et al, 1994b;OsterheldHaas et al, 1994). Instead, excess of extracellular 5-HT in monoamine oxidase (MAO)-A knock-out (ko) mice results in the complete absence of cortical barrel patterns, as shown by Nissl or cytochrome oxidase (CO) staining.…”
mentioning
confidence: 99%
“…Depletion of serotonin delays the development of the barrel fields of the rat somatosensory cortex 7,8 and decreases the size of the barrel fields. 9 Conversely, increased serotonin during this critical period, as in the monoamine oxidase A (MAOA) knock-out mouse, results in increased tangential arborization of these axons resulting in blurring of the boundaries of the cortical barrels. 10 Expression of a polymorphism of the serotonin transporter in autism 11,12 may result in altered serotonin modulation of thalamo-cortical connectivity, thus possibly accounting for abnormal sensory perception reported in many autistic subjects.…”
mentioning
confidence: 99%
“…13 Decreased or increased brain serotonin during this period of development results in disruption of synaptic connectivity in sensory cortices. 4,9,10 The effect of serotonin on synaptogenesis is not limited to the sensory cortices. For example, Yan et al 14 have reported that depletion of serotonin with PCA or 5,7-dihydroxytryptamine in neonatal rat pups resulted in large decreases in the numbers of dendritic spines in hippocampus.…”
mentioning
confidence: 99%